Taxonomic Analysis of Some Edible Insects From the State of Michoacán, Mexico - Pino Moreno, José Manuel; Blasquez, Julieta Ramos-Elorduy (Frontiers in Veterinary Science, 2021)
In the state of Michoacán, Mexico, 49 genera and 69 species of edible insects were registered; they belong to the Orders: Orthoptera: Families Pyrgomorphidae (2 species), Acrididae (5); Hemiptera-Heteroptera: Coreidae (1), Corixidae (2), Pentatomidae (2), Membracidae (2), Aethalionidae (3); Coleoptera: Cerambycidae (1), Cicendelidae (2), Curculionidae (2), Dytiscidae (1), Noteridae (1), Gyrinidae (1), Passalidae (1), Scarabaeidae (1), Tenebrionidae (2), Bostrichidae (1), Buprestidae (1), Melolonthidae (1); Lepidoptera: Cossidae (1), Danaidae (1), Megathymidae (1), Pieridae (1), Bombycidae (1), Sessidae (1), Noctuidae (1), Nymphalidae (1); Diptera: Stratiomydae (2) and Hymenoptera: Diprionidae (2), Apidae (10), Formicidae (4) and Vespidae (12). The Order Coleoptera presents the highest number of families (12), but the Order Hymenoptera the highest number of genera (18) and species (28), twelve of which belong to the Family Vespidae. Among the genera, 75.52% are monospecific, 14.28% bispecific, 4.08% trispecific, 4.08% tetraspecific and 2.04% pentaspecific. Their distribution by localities is indicated; these localities correspond to the municipalities of the state so far sampled; likewise, we report various forms in which they are prepared and the economic importance of the grasshoppers of the genus Sphenarium that are widely looked for, collected, accepted as part of the diet, consumed and marketed.